Strategy-making and organizational evolution : a managerial agency perspective - Burgelman, Robert A.; Snihur, Yuliya; Thomas, Llewellyn Douglas William (Cambridge : Cambridge University Press, 2023)
This element explains the role of the CEO in maintaining and updating the internal selection environment and contributing to organizational evolution, as well as making fundamental decisions about organizational splits of the firm's business models as an ecosystem evolves.
Also issued in print: 2023.
Includes bibliographical references.
Specialized.
Description based on online resource; title from PDF title page (viewed on April 12, 2023).
Keywords: Organizational change; Strategic planning; Business planning